The Pomeranian National Institute for the Deaf and Speech-Impaired in Wejherowo, 1921–1939. Introduction to research - Pękowska, Marzena (Biuletyn Historii Wychowania, 2018)
In the interwar period there was an intensive development of the theory and practice of pedagogy in Poland. At that time new schools and centers for children with disabilities were created, including for the deaf-mute. In 1921 the Pomeranian National Institute for the deaf and mute was established in Wejherowo. The paper presents the circumstances of the institution’s creation, its organization, rules of admission for pupils, curriculum and social life. Also provided is information on the authority of the Department and the teaching staff. In order to discuss these issues, source materials, stored in the Gdynia branch of the State Archive in Gdansk and held by the Educational-Instructional Centre for the Deaf Mute No. 2 in Wejherowo were used.